2006
DOI: 10.12968/ijtr.2006.13.8.370
|View full text |Cite
|
Sign up to set email alerts
|

Observations of activity levels and social interaction in a residential care setting

Abstract: Immobility, inactivity and the lack of social interaction are associated with poor physical and mental health. The main aim of this study was to examine the type and frequency of activities and social interactions with took place in a care home for older people. Residents within the communal area of a care home were observed over a period of 16 hours at 10-minute intervals by two psychologists. Residents' positions, activities and interactions were recorded. The majority of observations (97%) found residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…An observational study conducted in a care home for older people that recorded activity in 10-minute intervals over a 16-hour period found that the residents spent most of their time sitting (97% of observations) and not engaged in activity (60.7% of observations); social interaction between residents or with a caregiver occurred infrequently (10.7% of observations) [5]. Therefore, care-home residents spend the majority of their time inactive, with low levels of interaction with staff [5,6] and are dependent on staff to engage in daily occupations [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study conducted in a care home for older people that recorded activity in 10-minute intervals over a 16-hour period found that the residents spent most of their time sitting (97% of observations) and not engaged in activity (60.7% of observations); social interaction between residents or with a caregiver occurred infrequently (10.7% of observations) [5]. Therefore, care-home residents spend the majority of their time inactive, with low levels of interaction with staff [5,6] and are dependent on staff to engage in daily occupations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, care-home residents spend the majority of their time inactive, with low levels of interaction with staff [5,6] and are dependent on staff to engage in daily occupations [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Observational studies suggest that 97% of daytime is spent sedentarily by residents of nursing homes, e.g., sitting and watching TV with low levels of interaction with each other and with medical staff [38]. A lack of engagement with PA has a detrimental effect on physical and mental health, quality of life and social isolation [39].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study from Oxfordshire found that residents, including those capable of independent ambulation, spent the majority of their time sitting doing nothing. 5 Prolonged insufficient physical activity can induce muscle atrophy, incontinence, 6 pressure sores, 7 depression 8 and psychological distress. 9 There is clearly a need to keep long-term care home residents as active as possible.…”
Section: Introductionmentioning
confidence: 99%